(3COH GdfOjes - (3cTGLe , eMehO Hf GdMSjf Hf GdSfOj Hf TGgc, CHh GdaJM,J (B360 (3g` s ((3eSYhO Hf eMeO Hf ZGRj s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg aEfj hLOJ ef JbOe ef GdYdeGA hYfj HJCdja GdcJH ef GdCOHGA bO LQOhG HPcQ GdTQGH cJHkG VefhgG heSGQg eG GSJZQbhG ajg GdeYfi hGSJhahG Hg GdeOi s
(3BNQgG (B:s
(3EPG bdJ de JaYd hdjSJ eWjYkI hCaYd eG bGdJ aUQJ dgG YHOG GfJgi HfG Gdbhd Edi gPg GdZGjI haj HYV eG bOefG caGjI eDda GdcJGH ef GdeWGYf hjSJgOa dg ef GdeYGFH Ef TGA Gddg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B43 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B159s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B17 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdCgdjI HHGQjS (B(3301) s
Keywords: (3GdCOHs